(untitled) (Fiep Bulletin - online, 2013)
Chronic Obstructive Pulmonary Disease (COPD) is a disease of high mortality, characterized by airflow obstruction. The deterioration is typical of the disease interspersed with periods of exacerbation of symptoms (dyspnoea, cough and sputum), known as exacerbations. The care of COPD is not limited to pharmacologic therapy and self-management is an important item of educational programs for patients. Self-management is the term applied to any form of educational program aimed at teaching skills needed to make behavior change. Objective: To assess the impact of education for self-management of COPD participating in a pulmonary rehabilitation program-PRP. Methodology: Case Study with COPD PRP-Hospital Santa Cruz. All answered a questionnaire to obtain demographic and clinical data and other content specific questionnaire addressing Manual of COPD, in 03 steps: (Q1) questionnaire application and delivery of the Manual; (Q2) the questionnaire and read the manual to the patient; (Q3) the questionnaire. Results: We evaluated 16 patients with COPD, of both gender, low education, 65.69 ± 7.93 years, BMI 25.29 ± 6.76. About the aspects analyzed in the questionnaires: definition of COPD (8 right Q1, Q2 and Q3 8:09 right); symptom exacerbation of the crisis-"shortness of breath" (13 patients Q1, Q2 and Q3 12 patients); measure taken in relapsing "call in to the doctor" (5 patients Q1, Q2 and Q3 8 6 patients), physical exercises (15 right Q1, Q2 and Q3 16 right); intake of vegetables (16 right in 03 questionnaires); consumption of salt and foods with high calorie and water remained negative result. Conclusion: The data show that delivery of the Manual of COPD isolated and reading this, there was added to the COPD knowledge about the existing contents there in.